Lactate kinetics at the lactate threshold in trained and untrained men - Messonnier, Laurent A.; Emhoff, Chi-An W.; Fattor, Jill A.; Horning, Michael A.; Carlson, Thomas J.; Brooks, George A. (Journal of applied physiology (1985), 2013)
To understand the meaning of the lactate threshold (LT) and to test the hypothesis that endurance training augments lactate kinetics [i.e., rates of appearance and disposal (R a and R d , respectively, mg·kg −1 ·min −1 ) and metabolic clearance rate (MCR, ml·kg −1 ·min −1 )], we studied six untrained (UT) and six trained (T) subjects during 60-min exercise bouts at power outputs (PO) eliciting the LT. Trained subjects performed two additional exercise bouts at a PO 10% lower (LT-10%), one of which involved a lactate clamp (LC) to match blood lactate concentration ([lactate] b ) to that achieved during the LT trial. At LT, lactate R a was higher in T (24.1 ± 2.7) than in UT (14.6 ± 2.4; P < 0.05) subjects, but R a was not different between UT and T when relative exercise intensities were matched (UT-LT vs. T-LT-10%, 67% V̇o 2max ). At LT, MCR in T (62.5 ± 5.0) subjects was 34% higher than in UT (46.5 ± 7.0; P < 0.05), and a reduction in PO resulted in a significant increase in MCR by 46% (LT-10%, 91.5 ± 14.9, P < 0.05). At matched relative exercise intensities (67% V̇o 2max ), MCR in T subjects was 97% higher than in UT ( P < 0.05). During the LC trial, MCR in T subjects was 64% higher than in UT ( P < 0.05), in whom %V̇o 2max and [lactate] b were similar. We conclude that 1) lactate MCR reaches an apex below the LT, 2) LT corresponds to a limitation in MCR, and 3) endurance training augments capacities for lactate production, disposal and clearance.